(untitled) (Cultura Económica, 2019)
The article analyzes the current global economic development since the crisis of the mortgages of 2008, which outlines the end of the neoliberal paradigm. Facing weak republican democracies, the strong States of the emerging countries and BRIC have become the global economic driving force. The author examines the precise case of China and Russia, central models of the strong States, and then studies the developmental strategies of Brazil and Argentina. These cases illustrate that in the new forms of economic organization, strong States are the main core. Observing this fact in the light of the Social Doctrine of the Church, the author indicates the risk that this implies to the detriment of the democratic system, where the center of the economy is the human being.